2008
DOI: 10.1007/s00417-007-0757-4
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipases A2 in normal human conjunctiva and from patients with primary open-angle glaucoma and exfoliation glaucoma

Abstract: These findings demonstrate that sPLA(2)-IIA, sPLA(2)-V, iPLA(2) and cPLA(2) are expressed in the conjunctiva of non-glaucomatous patients. In the epithelium, sPLA(2)-IIA, sPLA(2)-V, and cPLA(2) may participate in protection against risks caused by mechanical wear and tear stress whereas iPLA(2) may regulate remodeling and maintenance of membrane phospholipids. sPLA(2)-IIA may also have the important role in the degradation of bacteria. In conjunctival stroma of POAG and ExG patients, sPLA(2)-IIA may play a rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…There is only a little knowledge about PLA 2 expression in other parts of the eye, in addition to the retina (Castagnet and Giusto, 1993; Van Themsche et al, 2001; Kolko et al, 2007). cPLA has been identified in the human cornea (Landreville et al, 2004), while, in the conjunctiva, cPLA 2 is mainly localized in the surface of the epithelium, probably participating in the protection against risks caused by mechanical wear and tear stress (Helin et al, 2008). In an in vitro retinoblastoma human triple culture model of angiogenesis, tumor cells induced in human retinal endothelium the increase in cPLA 2 proteinexpression (Lupo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…There is only a little knowledge about PLA 2 expression in other parts of the eye, in addition to the retina (Castagnet and Giusto, 1993; Van Themsche et al, 2001; Kolko et al, 2007). cPLA has been identified in the human cornea (Landreville et al, 2004), while, in the conjunctiva, cPLA 2 is mainly localized in the surface of the epithelium, probably participating in the protection against risks caused by mechanical wear and tear stress (Helin et al, 2008). In an in vitro retinoblastoma human triple culture model of angiogenesis, tumor cells induced in human retinal endothelium the increase in cPLA 2 proteinexpression (Lupo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…35 Moreover, sPLA 2 group IIA (sPLA 2 -IIA) has been shown to be significantly increased in tissue derived from POAG patients when compared to healthy controls. 24,64 Similarly PLA 2 -IIA expression has been shown to increase after ischemic events in the brain. PLA 2 -IIA is also known as the inflammatory sPLA 2 and increased levels of sPLA 2 -IIA occur in various inflammatory diseases and also in the brain, instigating neuronal cell death.…”
Section: The Possible Role Of Cyclooxygenase-2 Prostaglandins Amentioning
confidence: 99%
“…We have previously also shown that the expression of sPLA 2 ‐IIA was significantly increased in the conjunctival stroma of POAG and ExG patients (Helin et al. ). In the present study, the expression levels of ox‐LDL were generally increased in patient samples and we also observed dense ox‐LDL particles in the stroma.…”
Section: Discussionmentioning
confidence: 75%
“…; Helin et al. ). sPLA 2 ‐IIA has been linked as a prognostic biomarker for atherosclerosis (Divchev & Schieffer ).…”
Section: Discussionmentioning
confidence: 97%